Reflexiones entorno al programa de intervención en el asesoramiento vocacional para la elección de carrera con alumnos(as) del quinto año de secundaria· - Carrillo de Sánchez Málaga, Amalia (2011)
The present article presents the general alignments of an "lntervention Program in the Career Advice" according to the :nte rest s and abilities of the fifth grade high school students. Furthermore, it covers the educational offer and the labor market demands. The research analyses the impact of the applied program to a medium class parochial school students